2018
DOI: 10.1039/c8sc04092c
|View full text |Cite
|
Sign up to set email alerts
|

Atomically precise Au144(SR)60 nanoclusters (R = Et, Pr) are capped by 12 distinct ligand types of 5-fold equivalence and display gigantic diastereotopic effects

Abstract: Short-thiolate-protected Au144(SR)60 clusters are capped by 12 distinct ligand types of 5-fold equivalence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 66 publications
2
37
0
Order By: Relevance
“…The IonCCD mounted 1′′ away from the RWMA showed two major peaks corresponding to singly charged Au 144 (SC 4 H 9 ) 60 + ions ( m / z =33.7k; Figure A). Additionally, we observed minor signals of Au 144 (SC 4 H 9 ) 60 2+ ( m / z= 16.9k) and Au 144 (SC 4 H 9 ) 60 3+ ( m / z= 11.2k) at larger radii, which agrees with previously reported charge‐state distributions of Au 144 (SR) 60 in ESI‐MS . The results obtained at different frequencies of the rotating field are shown in Figure S4.…”
Section: Figuresupporting
confidence: 90%
“…The IonCCD mounted 1′′ away from the RWMA showed two major peaks corresponding to singly charged Au 144 (SC 4 H 9 ) 60 + ions ( m / z =33.7k; Figure A). Additionally, we observed minor signals of Au 144 (SC 4 H 9 ) 60 2+ ( m / z= 16.9k) and Au 144 (SC 4 H 9 ) 60 3+ ( m / z= 11.2k) at larger radii, which agrees with previously reported charge‐state distributions of Au 144 (SR) 60 in ESI‐MS . The results obtained at different frequencies of the rotating field are shown in Figure S4.…”
Section: Figuresupporting
confidence: 90%
“…[18] Owing to its distinct electrochemical, [18] optical, [19] biological, [20] and catalytic properties, [21] Au 144 (SR) 60 (Figure 2 A) is one of the most widely studied thiolated gold clusters. Previous studies employed ESI-MS to determine the composition of atomically precise Au 144 (SR) 60 clusters; [22,23] structural characterization was performed using scanning transmission-electron microscopy (STEM), [24] nuclear magnetic resonance, [22] single-crystal X-ray diffraction, [25] and theoretical calculations. [22,24,26] In this experiment, we do not attempt to separate this cluster from a mixture, but rather demonstrate that a specific charge state of the Au 144 (SR) 60 cluster may be deposited onto a surface for subsequent structure determination.…”
mentioning
confidence: 99%
“…16 Later, a combination of experimental and computational work by Maran and collaborators suggested that hydrogen-gold interactions may be present also in gold clusters stabilized by short alkylthiolates. 17 In this work we have employed massively parallel molecular dynamics simulations, with the interatomic forces calculated from DFT, to study the dynamics of the weak interactions in Au 68 (m-MBA) 32 and Au 144 (m-MBA) 40 at elevated temperatures. We show that the average atomic structure of the gold core corresponds well to the 3D reconstruction from the EM data.…”
mentioning
confidence: 99%